Growth of Cecropia hololeuca in water blades and substrates formulated with sewage sludge. - MORGADO, Bruna Tavares (2020)
Organic waste can be used in the production of forest seedlings, providing a high index of nutrients for them and contributing to the environment because it is a reused residue. Thus, this study aimed to evaluate the use of combined substrates with sewage sludge and water blades in embaúba seedlings. Treatments were: T1: 100% commercial substrate (CS), T2: 100% composted sewage sludge (CSS), T3: 75% CS and 25% CSS, T4: 75% CSS and 25% CS, and T5: 50% CSS and 50% CS. Three types of irrigation were provided four times a day, and the amount of water was: L1 – 9 mm, L2 – 18mm, and L3 – 27 mm. The evaluated parameters were plant height, leaf diameter, number of leaves and dry mass production. Results showed that the formulation of CSS and CS helped the development of the evaluated parameters. The best treatments found were T3 and T4 along the water blade 3.